DIE SUID-AFRIKAANSE OORLOGSEKONOMIE GEDURENDE DIE TWEEDE WERELDOORLOG - DEEL I - Vd B. Breedt, J. (Scientia Militaria - South African Journal of Military Studies, 2012)
There is a vast difference between the economies of a country during peace-time and a country at war. This article (to be published in two parts) analyses the South African economy during the Second World War with special reference to the changes and adaptation that it underwent from a peace-time to a war-time economy.